Peningkatan Keselamatan Kerja di Laboratorium IPA melalui Pelatihan Penggunaan Alat dan Praktikum Alat Sederhana - Taofik, De Budi Irwan; Mulyaningsih, Sri; Susila, Aceng Ahmad Rodian; Sidiq, Purnomo (IPI Press, 2023)
The laboratory is a facility or place where there are scientific activities (practicum/research) to produce a scientific product (result). The existence of a laboratory in schools is very necessary to support learning in the classroom. The main function of the Laboratory is to study and prove a particular theory and find or produce a scientific product (result). The laboratory is a practical facility for certain subjects that require practicum activities. Based on these facts, it is necessary to have good school laboratory management and pay attention to work safety factors. Knowledge of Occupational Health and Safety in the laboratory needs to be owned by all parties who will work in the laboratory so that accidents do not occur. The method used is in the form of exposure to material and an introduction to simple practicum by paying attention to OHS offline which contains an explanation of the basic concepts of work safety, sources of causes of work accidents, cases and how to control work safety in the laboratory. The data analysis technique used is descriptive. The result of this community service is the participants' understanding of how to carry out laboratory activities safely so that practicum activities in the school environment (SMP, SMA/MA) can be carried out smoothly and safely.